2015
DOI: 10.1088/0953-8984/27/26/265403
|View full text |Cite
|
Sign up to set email alerts
|

Di-hydrogen contact induced lattice instabilities and structural dynamics in complex hydride perovskites

Abstract: attempt to consider the question as to whether homopolar dihydrogen contacts may also be exploited, i.e. those between atoms of the same sign charge, for instance to geometrically engineer lattice instabilities in crystal lattices, alluding to other geometrical schemes applied to generate low symmetries in solids [2][3][4][5]. To investigate this, we choose one of the simplest and best known structure types known to solid state science, the ABX 3 perovskite. Perovskite functionalities are known to be extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 47 publications
6
35
0
Order By: Relevance
“…The formation of such bonds additionally enforce some charge delocalization within BH¨¨¨HB contacts (∆ρ 2 in Figure 2B), however, the overall BH¨¨¨HB interaction is destabilizing. Our conclusions are fully in line with the other, mostly experimental studies, in which the destabilizing role of BH¨¨¨HB interactions were also suggested [68][69][70][71][72]. McGrady and coworkers reported the opposite in their series of recent articles [17,20,21,29].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The formation of such bonds additionally enforce some charge delocalization within BH¨¨¨HB contacts (∆ρ 2 in Figure 2B), however, the overall BH¨¨¨HB interaction is destabilizing. Our conclusions are fully in line with the other, mostly experimental studies, in which the destabilizing role of BH¨¨¨HB interactions were also suggested [68][69][70][71][72]. McGrady and coworkers reported the opposite in their series of recent articles [17,20,21,29].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, we provided for the first time the energetic description of non-covalent interactions contributing to the stability of LiNMe 2 BH 3 and KNMe 2 BH 3 as well demonstrating, contrary to McGrady et al [29], the repulsive nature of the homopolar interactions BH¨¨¨HB. The latter is in line with numerous experimental papers [68][69][70][71][72]. Due to the fact that our calculations are based on the cluster approach as well as the fact that all theoretical methods are not free from approximations and very often not from arbitrariness, we believe that further works are needed from both theoretical and experimental laboratories in order to fully uncover the nature of homopolar BH¨¨¨HB interactions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The ordered description is supported, albeit not fully justified, by X-ray diffraction data collected down to temperatures of 100 K which did not show a change in diffraction pattern that would suggest a phase transition due to ordering. All reported phase transitions in borohydride perovskites occur above RT without any further events down to 100 K [4,19].…”
Section: Crystal Structure Of Nh4ca(bh4)3mentioning
confidence: 93%
“…H-H repulsion between the BH 4 − ligands may in some cases result in lower symmetry. [123,125]. Sodium zinc borohydrides are known in two compositions, NaZn(BH4)3 and NaZn2(BH4)5, which contain the complex ions [Zn(BH4)3] − and [Zn2(BH4)5] − , respectively.…”
Section: Bimetallic Borohydridesmentioning
confidence: 99%